Uma linguagem de programação quântica orientada a objetos baseada no featherweight java - Feitosa, Samuel da Silva (2016)
With the approaching end of Moore’s Law, where will not be possible to improve the capacity of silicon based processors, the quantum computing appear to be a good choice to provide a new era of computation. Quantum computing can be understood as the art of transform information encoded in the state of a quantum physical system. This encoding is through the quantum bits (qubits), which can be on superposition or entangled states, enabling to explore the property called quantum parallelism. In this work is discussed the creation of a quantum programming language implementing the object-oriented paradigm (OO), allowing manipulation of classes and objects, where the quantum effects are handled through a monadic approach, extending the Featherweight Java (FJ) proposal. This language is formally defined through the operational semantics, which allow the implementation in any language that provides closures. That language formalization enables us to create an interpreter, implementing the steps of lexical, syntactic and semantic analysis, focusing in the type system to embedded quantum computing concepts in a classical language. Several examples are provided in the text, showing ways to handle the monadic layer in order to perform transformations in quantum information.